Viraemia, immunogenicity, and survival outcomes of cytomegalovirus chimeric epitope vaccine supplemented with PF03512676 (CMVPepVax) in allogeneic haemopoietic stem-cell transplantation: randomised phase 1b trial. Issue 2 (February 2016) - Nakamura, Ryotaro; Rosa, Corinna La; Longmate, Jeffrey; Drake, Jennifer; Slape, Cynthia; Zhou, Qiao; Lampa, Melanie G; O'Donnell, Margaret; Cai, Ji-Lian; Farol, Len; Salhotra, Amandeep; Snyder, David S; et al.
Summary: Background: Patients seropositive for cytomegalovirus (CMV) and undergoing allogeneic haemopoietic stem-cell transplantation (HCT) are at risk for CMV reactivation. Stimulating viral immunity by vaccination might achieve CMV viraemia control without the need for antiviral agents. CMVPepVax is a chimeric peptide composed of a cytotoxic CD8 T-cell epitope from CMV pp65 and a tetanus T-helper epitope. It is formulated with the adjuvant PF03512676, a Toll-like receptor 9 agonist, which augments cellular immunity. We aimed to assess safety, immunogenicity, and possible clinical benefit of the CMVPepVax vaccine in patients undergoing HCT. Methods: We did a randomised, open-label, phase 1b trial at one transplant centre in the USA. Eligible patients were CMV-seropositive, positive for HLA-A*0201, aged 18–75 years, and undergoing HCT from a matched-related or matched-unrelated donor. Patients were reassessed for eligibility on day 28 after HCT. We randomly allocated patients to either the CMVPepVax vaccine or observation, in blocks stratified by CMV donor serostatus. CMVPepVax was administered subcutaneously on days 28 and 56. The primary outcome was safety, which consisted of secondary graft failure, grade III–IV acute GVHD, non-relapse mortality by day 100, serious adverse events related to the vaccine (judged by the data and safety monitoring committee [DSMC]) grade 3–4 adverse events related to the vaccine (judged by the DSMC) within 2 weeks of vaccination, and development of double-strand (ds) DNA autoantibodies. Statistical analyses included all randomised patients and were done per-protocol. This study is registered withClinicalTrials.gov, numberNCT01588015 . This trial is closed to accrual and the final analysis is presented in this report. Findings: Between Oct 31, 2012, and Nov 5, 2014, 36 eligible patients were allocated to either CMVPepVax (n=18) or observation (n=18), with no adverse effect on HCT (no secondary graft failures in either group) or cases of acute GVHD (seven patients assigned vaccine and six under observation had acute GVHD of grade 2 or less), and no unexpected adverse events. Compared with observation, better relapse-free survival was recorded in patients allocated the vaccine (seven vs one; hazard ratio [HR] 0·12, 95% CI 0·01–0·94; p=0·015). No patients had non-relapse mortality by day 100. One serious adverse event (grade 1 fever) was attributed to CMVPepVax but resolved within 48 h. Four patients assigned the vaccine had a serious adverse event, which was unrelated to the vaccine (grade 3 thrombocytopenia, grade 3 device-related infection, grade 2 nausea, and grade 1 fever), compared with nine patients under observation (grade 4 maculopapular rash, grade 3 nausea, grade 3 infection, grade 3 thrombotic thrombocytopenic purpurea, grade 2 nausea, grade 2 generalised muscle weakness, grade 2 infection, grade 1 fever, and grade 1 fatigue; p=0·16). 54 grade 3–4 adverse events were reported in patients assigned the vaccine compared with 91 in patients who were under observation (p=0·2). No patients had grade III–IV acute GVHD or developed dsDNA autoantibodies. Interpretation: The results show safety and immunogenicity of the CMVPepVax vaccine. The prospect of substantial clinical benefits warrant testing in a phase 2 trial. Funding: National Cancer Institute.